Metabolic and Bariatric Surgery Chapter of the Association of Polish Surgeons. Bariatric and metabolic surgery care standards - Jacek Szeliga; Mariusz Wyleżoł; Piotr Major; Andrzej Budzyński; Artur Binda; Monika Proczko-Stepaniak; Iwona Boniecka; Maciej Matłok; Marzena Sekuła; Łukasz Kaska; Piotr Myśliwiec; Tomasz Szewczyk; et al. (Videosurgery and Other Miniinvasive Techniques)
The Metabolic and Bariatric Surgery Chapter of the Association of Polish Surgeons (Polish acronym: SCMiB TCHP) is a Polish specialist scientific society representing bariatric surgeons as well as specialists from other disciplines and professions cooperating with them during the provision of services in the field of bariatric and metabolic surgery, as well as the entire care process before and after surgery. The following standards constitute the minimum requirements set by the SCMiB TCHP for good practice of the basic process of bariatric care throughout its entire period, which ensure satisfactory safety and effectiveness of the obesity treatment and its metabolic complications.